The Awareness Of Selected University Students About Nursing Care For Chemotherapy-Induced Peripheral Neuropathy (Journal of Pharmaceutical Negative Results, 2022)
Cancer management is a radical event that is accompanied by severe side effects related to the cancer itself or/and therapeutic interventions. Particularly, chemotherapy-induced peripheral neuropathy is the most prevalent neurological complication of chemotherapy. So that awareness of nursing students will play a crucial role in managing this painful condition. Objective: This study aimed to assess the awareness of selected university students about nursing care for chemotherapy-induced peripheral neuropathy in Ismailia City. Methods: A cross-sectional design was utilized with convenient samples that were recruited (622 students). Utilizing a self-administered questionnaire to assess the participants’ awareness about nursing care for chemotherapy-induced peripheral neuropathy. Results: The findings clarified that 52% were female and 38% had a mean age of 21. Most (58% of students) showed low levels of awareness. There was a statistically significant relationship found between the student's level of awareness about nursing care for chemotherapy-induced peripheral neuropathy and their demographic data (p <0.05). Conclusion: Obviously, less than half of the participant students were aged between 20-22 years, more than half of them were female. Furthermore, most of the participant students had a low level of awareness, and there were related factors such as place of residence, academic level, and affiliations. Recommendations: Consequently, continuous competent health education for students should be made to improve their level of awareness and their near-future roles. Further research studies are necessary to identify their educational needs and the factors that influence the university students' level of awareness related to CIPN.